Lack of Inclusive Employment Strategies for Persons with Disabilities: Policies and Initiatives to Promote the Inclusion of the Persons with Disabilities in the Labor Market - Alizada, Nuray; Aliyeva, Kifayat; Gahramanzade, Ordukhan (ADA University, 2024)
This capstone project aims to examine inclusive employment strategies for persons with disabilities (PWDs) in Azerbaijan as well as offer policy alternatives and initiatives to promote their inclusion into the labor market. Azerbaijan has been tackling the complex issues of disability and their inclusion into the labor market for decades. It also takes a prominent place in the national agenda of the country. The research has revealed that despite a number of projects and initiatives related to the protection and integration of the people with disabilities, the general public is not well informed about them. In the current study lack of effective inclusive education opportunities, societal attitudes, and misconceptions, inherent financial as well as infrastructure barriers have been identified as the main barriers in the inclusion of the people with disabilities into the labor market. In response to the above-mentioned challenges, the research proposes several policy alternatives such as arranging and developing special classes at educational institutions, conducting public awareness campaigns, provision of sheltered employment as well as reformation of the employment policies. These policy suggestions were further improved by the research as well as survey against five criteria: The paper concludes by providing the best policy suggestion as well as a set of recommendations that call for an urgent attention and collaboration of the government, public and private agencies as well as NGOs.
Keywords: Azerbaijan -- Social conditions -- 21st century.; Employment policies -- Azerbaijan.; Public awareness -- Azerbaijan; Inclusive education -- Azerbaijan; Persons with disabilities -- Employment -- Azerbaijan; Public and International Affairs